Multicasting, Regulation, and Public Value: Reconfiguring Public Broadcasting in Indonesia’s Digital Era - Fasta, Feni; Dwiana, Ressi; Widianti, Ezki Tri Rezeki (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2026)
This study addresses the persistent gap between technological transformation and the substantive realization of public service broadcasting in Indonesia’s digital television transition. Although digital migration has expanded multiplexing capacity and channel availability, it remains unclear whether these developments have strengthened the public service mandate of Televisi Republik Indonesia (TVRI). The research aims to examine how TVRI utilizes digital multicasting infrastructure to diversify channels, enhance content quality, and fulfill its public service obligations. This study employs a qualitative case study design. Data were collected through in-depth interviews with key institutional actors, policy analysis of broadcasting regulations, and systematic observation of TVRI’s digital channel programming. The analysis focuses on institutional capacity, regulatory frameworks, and patterns of content diversification and accessibility. The findings indicate that digitalization has significantly enhanced TVRI’s technical capacity, particularly in multiplexing management and channel expansion. However, this technical advancement has not been accompanied by a proportional transformation of content strategy. Channel diversification remains limited, accessibility features are inconsistently implemented, and educational specialization has not materialized as a dedicated service. Regulatory gaps and chronic budgetary constraints further restrict institutional innovation. The study concludes that technological migration alone is insufficient to achieve public service objectives without coherent governance reform, sustainable funding, and clear digital content mandates.